Hubungan Kontrol Diri Dengan Prestasi Belajar Siswa Kelas X SMA Kristen 1 Tomohon - Krisnover Temponbuka; Ariantje J.A. Sundah; Deklay Nainggolan (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the relationship between self-control and student achievement and is carried out through quantitative methods. The research subjects totaled 45 students drawn by random sampling technique. The research data were analyzed using a simple correlation technique, and the results of the data analysis found that the value of the r XY count was 0.427. Compared to the value of r XY table dk 45 at a significance level of 95% which is 0.294, it turns out that the calculated value of r XY is greater than the value of the r XY table or 0.427 > 0.294. These results mean that there is a significant relationship between self-control and student achievement. Thus the results of this test support the proposed hypothesis Ha so that it can be accepted, otherwise, hypothesis Ho is rejected. The power of determination of self-control variables with student achievement in class X SMA Kristen 1 Tomohon is 18%, while the remaining 82% is influenced by other factors not examined. These findings also indicate that individuals who have high self-control will be able to make decisions and take effective actions in order to produce what is desired and avoid unwanted negative consequences. So that these findings become the agenda for guidance and counseling services in schools, that guidance and counseling services to increase self-control really need to be implemented.